Identification and Characterisation of the Murine Homologue of the Gene Responsible for Cystinosis, Ctns - Cherqui, Stéphanie (BioMed Central, 2000)
BACKGROUND: Cystinosis is an autosomal recessive disorder characterised by an intralysosomal accumulation of cystine, and affected individuals progress to end-stage renal failure before the age of ten. The causative gene, CTNS, was cloned in 1998 and the encoded protein, cystinosin, was predicted to be a lysosomal membrane protein. RESULTS: We have cloned the murine homologue of CTNS, Ctns, and the encoded amino acid sequence is 92.6% similar to cystinosin. We localised Ctns to mouse chromosome 11 in a region syntenic to human chromosome 17 containing CTNS. Ctns is widely expressed in all tissues tested with the exception of skeletal muscle, in contrast to CTNS. CONCLUSIONS: We have isolated, characterised and localised Ctns, the murine homologue of CTNS underlying cystinosis. Furthermore, our work has brought to light the existence of a differential pattern of expression between the human and murine homologues, providing critical information for the generation of a mouse model for cystinosis.